Connecting the world through canals: an analysis of water infrastructure in diplomacy, economic relations, and sustainable development - Mohd Firdaus Abdullah,; Arba’iyah Mohd Noor,; Ismail Ali,; Noraini Mohamed Hassan,; Haslinda Hasan, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Canals have long been a crucial component in the development of world civilisations, functioning not only as water infrastructure but also as symbols of diplomacy, economic power, and sustainable development that transcend geopolitical boundaries. This article examines the strategic role of canals in linking global societies, strengthening international trade, and fostering cultural exchange from both historical and contemporary perspectives. Employing a qualitative approach, the study underscores the significance of waterways such as the Suez Canal, the Panama Canal, the Kra Canal and others, as both physical and symbolic conduits that facilitate social, economic, and political integration. The findings reveal that canals have accelerated global mobility, shaped major maritime trade networks, and acted as instruments of economic diplomacy. Nevertheless, persistent challenges including geopolitical rivalries, uneven distribution of economic benefits, and ecological vulnerabilities continue to constrain the potential of canals as catalysts for global cohesion. This article argues for enhanced ecological monitoring and the establishment of a more inclusive framework for international cooperation to mitigate these challenges. By situating canals within the context of climate change and sustainable development, it advances a new perspective on water infrastructure as a critical element of global integration, capable of supporting social, economic, and ecological interconnectedness at the international level, thereby making a significant contribution to the academic literature.